Prolonged QT Interval in Patients Receiving Psychotropic Medications. (July 2020) - Swenson, Rebecca S.; Murphy-Ende, Kathleen
INTRODUCTION: Prolonged QT interval (PQTI) is a cardiac condition widely documented in the mental health literature and linked to psychotropic medication use. Medications notable for contributing to the condition are antipsychotics, antidepressants, and some mood stabilizers. Although additional medication classes and other contributing risk factors are often present, the prudent mental health provider benefits from having a basic understanding of this condition and how to prevent and manage it with safe prescribing practices.AIMS: This guide seeks to provide mental health prescribers with a basic understanding of the risk factors, pathophysiology, identification, and management of PQTI.METHOD: Relevant literature and practice guidelines were reviewed and summarized with a focus on practical interventions for the psychiatric mental health nurse practitioner (PMHNP).RESULTS: One of the primary contributing factors to PQTI development and complications is polypharmacy. Patients with co-occurring medical, mental health, and/or substance use disorders may receive medications from multiple providers. Anticancer drugs, antiarrhythmic medications, and even a number of common antibiotics can increase the QT interval, making it a challenge for even the most experienced mental health provider to monitor medication interactions and side effects that contribute to PQTI. Having a sound knowledge base of these factors can guide safe PMHNP practice.CONCLUSIONS: Decision-making trees grounded in evidence-based research were developed in order to direct thorough assessment and safe treatment of patients requiring psychotropic medications.